CRITICAL REVIEW ON THE EXISTENCE OF TRANSGENERATIONAL ENTREPRENEURSHIP IN TOURISM BUSINESSES: CURRENT TREND AND INTEREST - Mohd Puzi, Mohd Alif; Ismail, Hairul Nizam (PLANNING MALAYSIA, 2017)
Tourism, one of Malaysia’s fastest growing economic sector, has created many business opportunities, the majority of which are family-controlled businesses. New ventures are started by founders who will eventually invite their relatives, especially as successors for their businesses. Nowadays, a successful family business is not determined by traditional methods alone such as profit, assets, or capital, but also take into account survivability or entrepreneurship transmission between generations. Unfortunately, entrepreneurship researchers have not fully embraced tourism because of the prevailing assumption that tourism is a just regular business. Both tourism and transgenerational entreprenership fields employ empirical studies to justify their idiosyncrasies but remain separate from each other. If studied together, it would lead to better understanding of both fields and would even spark the curiosity of researchers to investigate family relationships in conglomerate tourism businesses. Further research into this mixture of fields will also provide a conceptual economic model for tourism destination development bodies that will enhance and promote local community entrepreneurship.